Noninvasive prediction of portal pressure with MR elastography and DCE‐MRI of the liver and spleen: Preliminary results. Issue 4 (11th April 2018) - Wagner, Mathilde; Hectors, Stefanie; Bane, Octavia; Gordic, Sonja; Kennedy, Paul; Besa, Cecilia; Schiano, Thomas D.; Thung, Swan; Fischman, Aaron; Taouli, Bachir
Abstract : Background: Portal hypertension (PH), defined by hepatic venous pressure gradient (HVPG) ≥5 mmHg and clinically significant PH, defined by HVPG ≥10 mmHg, are complications of chronic liver disease. Purpose: To assess the diagnostic performance of MR elastography (MRE) and dynamic contrast‐enhanced MRI (DCE‐MRI) of the liver and spleen for the prediction of PH and clinically significant PH, in comparison with a qualitative PH imaging scoring system. Study Type: IRB‐approved prospective study. Population: In all, 34 patients with chronic liver disease who underwent HVPG measurement. Field Strength/Sequence: 1.5/3T examination including 2D‐GRE MRE ( n = 33) and DCE‐MRI of the liver/spleen ( n = 28). Assessment: Liver and spleen stiffness were calculated from elastogram maps. DCE‐MRI was analyzed using model‐free parameters and pharmacokinetic modeling. Two observers calculated qualitative PH imaging scores based on routine images. Statistical Tests: Imaging parameters were correlated with HVPG. Receiver operating characteristic (ROC) analysis was performed for prediction of PH and clinically significant PH. Results: There were significant correlations between DCE‐MRI parameters (liver time‐to‐peak, r = 0.517 / P = 0.006, liver distribution volume, r = 0.494 / P = 0.009, liver upslope, r = –0.567 / P = 0.002), liver stiffness ( r = 0.478 / P = 0.016), PH imaging score ( r = 0.441 / P = 0.009), and HVPG. ROC analysis provided significant area under the ROC (AUROCs) for PH (liver upslope 0.765, liver stiffness 0.809, spleen volume/diameter 0.746–0.731, PH imaging score 0.756) and for clinically significant PH (liver and spleen perfusion parameters 0.733–0.776, liver stiffness 0.742, PH imaging score 0.742). The ratio of liver stiffness to liver upslope had the highest AUROC for diagnosing PH (0.903) and clinically significant PH (0.785). Data Conclusion: These preliminary results suggest that the combination of liver stiffness and perfusion metrics provide excellent accuracy for diagnosing PH, and fair accuracy for clinically significant PH. Combined MRE and DCE‐MRI outperformed qualitative imaging scores for prediction of PH. Level of Evidence : 1 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2018;48:1091–1103.